Development of a modified Margaria-Kalamen anaerobic power test for American Football athletes - Hetzler, R. K; Vogelpohl, R. E; Stickley, C. D; Kuramoto, A. N; DeLaura, M. R; Kimura, I. F. (The Journal of Strength and Conditioning Research, 2010)
This study examined a modification of the Margaria-Kalamen test for football players. The football stair climb test (FST) protocol used in this study increased the vertical displacement (20 steps, 3.12 m) so that the mean best time for the test was 2.048 +/- 0.267 seconds. Fifty-eight Division I-A football players volunteered to participate (mean +/- SD age = 20.2 +/- 1.8 yr, height = 184.1 +/- 7.7 cm, weight = 102.5 +/- 19.4 kg). Subjects performed 25 trials with 30 to 40 seconds of rest between trials. Test-retest reliability was determined using 34 subjects by way of intraclass correlation coefficients with a value of 0.73 for peak power and SEM of 105.4 W, indicating an acceptable level of reliability. Subjects were divided into 3 groups by position: linemen (Line), skill, and linebackers (LB). Alpha level was p < 0.05. Peak power was 1674.5 +/- 300.8, 1712.6 +/- 251.5, and 1388.6 +/- 210.4 W for the LB, Line, and Skill groups, respectively. Groups were significantly different (p < 0.0001), with the LB and Line found to be more powerful than the Skill group. Peak power continued to increase throughout the 25 trials in the Skill and LB group but plateaued after approximately 17 trials in the Line group. It was concluded that the FST was a reliable test for measuring peak anaerobic power in collegiate football players, which, theoretically, should provide more accurate measures of peak power caused by increased vertical displacement and longer duration, resulting in a decreased influence of cheating strategies during test administration. To achieve maximal power in stair climbing tasks, coaches may need to incorporate a greater number of trials or a more intense warm-up than has been previously reported.